PERANCANGAN SISTEM INFORMASI POKTAN BERBASIS MOBILE (STUDI KASUS DI POKTAN BENO RAHARJO, GLONGGONG, BALEREJO, KABUPATEN MADIUN - Anggyanisa Mutia Putri; Hari Murti (Elkom : Jurnal Elektronika dan Komputer, 2023)
Agriculture is an activity of managing biological natural resources with the help of technology, capital, labor and management to produce agricultural commodities which include food crops, horticulture, plantations and or livestock in an agro-ecosystem. Most of the Indonesian people's livelihoods are as farmers, so the agricultural sector is very important to develop in this country. Poktan Beno Raharjo in Glonggong Village, Madiun Regency has a problem, namely the absence of an information system that is useful for managing agricultural production data, managing farmer data, managing village granary data, recording planting of food crops and horticultural crops, managing subsidized fertilizer assistance. The mobile-based Poktan information system was created using the dart programming language with the flutter framework using the waterfall method and testing using the black box testing method.